Документи радянських спецслужб з історії кримськотатарського національного руху 1940-х – 1980-х рр. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The documents of the Branch state archive of Security service of Ukraine shed the light on the range of controversial questions and unclarified pages of Crimean Tatars’ history of the 2d half of 1940th – 1980th. The published documents discover how the preparion for the deportation of Crimean Tatars was held; show the fight of unsubdued nation to return its homeland; investigated the position of Soviet party authority about Crimean Tatars problem and methods they used to subdue national movement.